ALCAM and VCAM-1 as urine biomarkers of activity and long-term renal outcome in systemic lupus erythematosus. (13th November 2019) - Parodis, Ioannis; Gokaraju, Sirisha; Zickert, Agneta; Vanarsa, Kamala; Zhang, Ting; Habazi, Deena; Botto, João; Serdoura Alves, Clara; Giannopoulos, Panagiotis; Larsson, Anders; Svenungsson, Elisabet; Gunnarsson, Iva; et al.
Abstract: Objectives: We investigated the cell adhesion molecules (CAMs) Vascular CAM 1 (VCAM-1) and Activated Leucocyte CAM (ALCAM) as urinary biomarkers in SLE patients with and without renal involvement. Methods: Female SLE patients ( n  = 111) and non-SLE population-based controls ( n  = 99) were enrolled. We measured renal activity using the renal domain of the BILAG index and urine (U) and plasma (P) concentrations of soluble (s)VCAM 1 and U-sALCAM using ELISA. U-sCAM levels were next corrected by U-creatinine. Results: U-sVCAM-1/creatinine and U-sALCAM/creatinine ratios were higher in SLE patients vs non-SLE controls ( P  < 0.001 for both), as well as in patients with active/low-active (BILAG A–C; n  = 11) vs quiescent (BILAG D; n  = 19) LN ( P  = 0.023 and P  = 0.001, respectively). U-sALCAM/creatinine but not U-sVCAM-1/creatinine ratios were higher in patients with nephritis history (BILAG A–D; n  = 30) vs non-renal SLE (BILAG E; n  = 79) ( P  = 0.014). Patients with baseline U-sVCAM-1/creatinine ratios ≥75th percentile showed a 23-fold increased risk of a deterioration in estimated glomerular filtration rate by ≥25% during a 10-year follow-up (odds ratio: 22.9; 95% CI: 2.8, 189.2; P  = 0.004); this association remained significant after adjustments for age, disease duration and organ damage. Traditional markers including anti-dsDNA antibodies did not predict this outcome. Conclusion: While high U-sVCAM-1 levels appear to reflect SLE disease activity, sALCAM might have particular importance in renal SLE. Both U-sVCAM-1 and U-sALCAM showed ability to distinguish SLE patients with active renal involvement from patients with quiescent or no prior nephritis. High U-sVCAM-1 levels may indicate patients at increased risk for long-term renal function loss.